THE DIFFERENCES IN MORPHOLOGICAL CHARACTERISTICS AND MOTOR ABILITIES MALE AND FEMALE STUDENTS OF THE SECOND GRADE OF PRIMARY SCHOOL - THE DIFFERENCES IN MORPHOLOGICAL CHARACTERISTICS AND MOTOR ABILITIES MALE AND FEMALE STUDENTS OF THE SECOND GRADE OF PRIMARY SCHOOL (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The aim of this research was to establish the differences in some morphological characteristics and motor abilities between male and female students from the second grade of primary school. 153 tested students (74 male and 79 female students) from the primary schools in Trstenik were tested for the research. Morphological characteristics were estimated according to three variables (body height, body weight and body mass index) and motor abilities were estimated according to seven variables (keeping in pull-up position, long jump from standing start, the throwing of medicine ball, forward bend on a bench, 30 m dash from a flying start, 300 m run, agility on the floor). The differences between the primary school male and female students were estimated according to the multivariant analysis of variance and discriminative analysis. The results of the research showed that statistically there were no significant differences between the male and female students from the second grade of primary school when morphological characteristics were concerned, while in the area of motor abilities there were differences which are statistically significant